2021
DOI: 10.3389/fpubh.2021.682634
|View full text |Cite
|
Sign up to set email alerts
|

Social-Ecological Factors Associated With Higher Levels of Resilience in Children and Youth After Disaster: The Importance of Caregiver and Peer Support

Abstract: Children and youth are among the most vulnerable to the devastating effects of disaster due to the physical, cognitive, and social factors related to their developmental life stage. Yet children and youth also have the capacity to be resilient and act as powerful catalysts for change in their own lives and wider communities following disaster. Specific factors that contribute to resilience in children and youth, however, remain relatively unexplored. This article examines factors associated with high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…In contrast, we found that peer support was positively associated with resilience in adolescents with T1D. This result coincided with previous studies in which a positive association between peer support and resilience was observed among youth who experienced disasters [ 36 ] or early left behind [ 37 ]. A qualitative study showed that emotional and self-management support from peers who also had T1D was important for adolescents in fighting the disease and obtaining resilience [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, we found that peer support was positively associated with resilience in adolescents with T1D. This result coincided with previous studies in which a positive association between peer support and resilience was observed among youth who experienced disasters [ 36 ] or early left behind [ 37 ]. A qualitative study showed that emotional and self-management support from peers who also had T1D was important for adolescents in fighting the disease and obtaining resilience [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…(Vivian) Identifying and attacking the problem rather than each other, as well as showing understanding and compassion to one another, helped families create safe spaces where members could identify and resolve conflict in a constructive way. These findings support existing research that indicates that conflict resolution strategies influence the family environment post-disaster, with parents playing an important role in overall family functioning, and specifically in positive mental health among children (Cobham et al, 2016;McDonald-Harker et al, 2021b).…”
Section: Empathy and Compassion To Create Safe Spacessupporting
confidence: 87%
“…These recommendations may be especially pertinent for crises such as COVID-19, which require safety measures that restrict social contact. The desire for individuals to connect during challenging experiences is well documented also for contexts beyond communicable diseases or limited social contact (Shigemoto & Kawachi, 2020 ; McDonald-Harker et al, 2021 ). For further insight into the extent to which our participants’ recommendations apply to crises beyond COVID-19, future studies can adapt our procedures to investigate RRTPs’ responses to non-COVID-19 threats, then compare resulting recommendations to our findings.…”
Section: Discussionmentioning
confidence: 99%